TEKNOLOGI MENGIRIMKAN DATA AUDIO MENGGUNAKAN CAHAYA LASER 5MW 650NM - Longges, Rival (Universitas Islam Balitar Blitar, 2025)
Visible Light Communication (VLC) is a wireless communication technology that utilizes visible light as a medium for transmitting information. This study develops a VLC-based audio communication system using a laser diode (LD) as a transmitter and a solar panel as an audio signal receiver. This system is designed to evaluate the performance of voice transmission in various lighting conditions (bright and dark), distances (1–48 meters), and variations in the angle of light transmission and reflection. The test results show that the system is able to transmit audio stably up to a distance of 48 meters, both in bright and dark conditions. However, the sound quality received tends to be higher and more stable in dark conditions, with an average dB value above 90 dB, and minimal interference from environmental light. In addition, high tones such as la, sol, and si show the best quality in both conditions. The test of the beam angle and reflection through the mirror also proved that the system remains effective even though the angle and distance increase, especially in low light intensity environments. From the overall results, this laser-based VLC system is proven to be an efficient, power-saving, and electromagnetic interference-resistant wireless audio communication alternative, and is very suitable for use in dark indoor environments or areas sensitive to radio waves. Keywords: Visible Light Communication, laser diode, solar panel, audio communication, light intensity, sound quality.management